Knowledge, Attitudes and Acceptability of Cervical Cancer Screening among Public School Teachers in Benin Metropolis - Igudia, Enoma Omorogieva; Omon-Dave, Rachael Osariemen; Uwadie, Wesley Choice (NIU Journal of Social Sciences, 2025)
This study was designed to investigate knowledge, attitudes and acceptability of cervical cancer screening among public school teachers in Benin Metropolis. Five research questions were raised to guide the study, while two hypotheses were formulated and tested at 0.05 level of significance. The descriptive survey research design was adopted for the study. The population for this study consisted of all the 2,120 public school teachers in Benin Metropolis. The sample size for the study was381 respondents and was selected through multi-stage sampling technique.  A self-structured questionnaire designed by the researchers and validated by three experts in HSE department was used for the study. Two research assistants who were briefed of the purpose of the study assisted the researchers to administer the questionnaire to the respondent, only 361 copies were retrieved successfully after completion. Data collected was analyzed using frequency counts and percentages for the research questions while the inferential statistics of Chi-square was used to test the hypotheses at 0.05 level of significance. The findings from the study showed that most (63.9%) of the public-school teachers in Benin Metropolis had moderate knowledge of cervical cancer screening. Majority (70.9%) of respondents have positive attitudes towards cervical cancer screening and their level of acceptability is also high (60.11%). The study further revealed that knowledge significantly influenced acceptability of cervical cancer screening among public school teachers in Benin metropolis but attitudes did not. Based on the findings of the study, it was recommended among others that government should carryout educational campaigns and increase efforts to enhance knowledge about cervical cancer screening. Keywords: Knowledge, attitudes, acceptability, cervical cancer screening, Benin Metropolis